2007
DOI: 10.1152/ajpheart.00514.2007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cell types and numbers during cardiac development in the neonatal and adult rat and mouse

Abstract: Cardiac fibroblasts, myocytes, endothelial cells, and vascular smooth muscle cells are the major cellular constituents of the heart. The aim of this study was to observe alterations in myocardial cell populations during early neonatal development in the adult animal and to observe any variations of the cardiac cell populations in different species, specifically, the rat and mouse. Whole hearts were isolated from either mice or rats during the neonatal and adult stages of development, and single cell suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
463
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(491 citation statements)
references
References 33 publications
(103 reference statements)
19
463
2
7
Order By: Relevance
“…Other types of cells, such as those in vasculature and connective tissues, (Manabe et al, 2002), are not considered. Recent studies have revealed that fibroblasts, as one kind of connective tissue, are the most abundant cell type by number in cardiac tissues, comprising about 70% of all cells (Banerjee et al, 2007). Because of their small size, they make up only about 6% of the total cardiac volume (Rossi, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other types of cells, such as those in vasculature and connective tissues, (Manabe et al, 2002), are not considered. Recent studies have revealed that fibroblasts, as one kind of connective tissue, are the most abundant cell type by number in cardiac tissues, comprising about 70% of all cells (Banerjee et al, 2007). Because of their small size, they make up only about 6% of the total cardiac volume (Rossi, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The mouse heart is composed of ~56% cardiomyocytes, 27% fibroblasts, 10% vascular smooth muscle cells and 7% endothelial cells (Banerjee et al, 2007). Most likely, several other cell types are hidden within these principal groups awaiting further characterization.…”
Section: Cell Types In Heart and Their Lineagesmentioning
confidence: 99%
“…Rat hearts contain only 26.4% cardiomyocytes, a number that is similar to human beings. The major cell type in rat and human hearts is the fibroblast (62.6%) (Banerjee et al, 2007;Nag, 1980). If we look at the composition of cell types in the heart, rats appear to be rather similar to humans (Rubart & Field, 2006).…”
Section: Cell Types In Heart and Their Lineagesmentioning
confidence: 99%
“…This happens, in this phase, because, in contrast with the adult muscle, the muscle and interstitial cells divide actively 14,15 . Our findings suggest that, in the pubescents, the passive growth predominates in relation to the cellular proliferation, while in the infants the two components prevail.…”
Section: Major Findingsmentioning
confidence: 99%